Comparison of culture-dependent and independent approaches to characterize fecal bifidobacteria and lactobacilli. (April 2016) - Quartieri, Andrea; Simone, Marta; Gozzoli, Caterina; Popovic, Mina; D'Auria, Giuseppe; Amaretti, Alberto; Raimondi, Stefano; Rossi, Maddalena
Abstract: Different culture-dependent and independent methods were applied to investigate the population of bifidobacteria and lactobacilli in the feces of five healthy subjects. Bacteria were isolated on MRS, a complex medium supporting growth of lactobacilli and bifidobacteria, and on three selective media for bifidobacteria and two for lactobacilli. Taxonomic characterization of the isolates was carried out by RAPD-PCR and partial 16S sequencing. The selectivity of genus-specific media was also investigated by challenging colonies from MRS plates to grow onto each medium. In parallel, a quantitative and qualitative description of bifidobacteria and lactic acid bacteria was obtained by FISH, qPCR, TRFLP, and 16S rRNA gene sequencing. Bifidobacteria did not fail to grow on their specific media and were easily isolated and enumerated, showing comparable quantitative data among culture-dependent and -independent techniques. The Bifidobacterium species identified on plates and those extracted from TRFLP and 16S rRNA gene sequencing were mostly overlapping. Selective media for lactobacilli gave unsuitable results, being too stringent or too permissive. The quantification of lactobacilli through selective plates, qPCR, FISH, and 16S rRNA gene sequencing gave unreliable results. Therefore, unlike bifidobacteria, intestinal lactobacilli are still problematic in terms of quantification and accurate profiling at level of species and possibly of strains by both culture-dependent and culture-independent techniques. Highlights: Culture-dependent and independent methods were compared to describe fecal bifidobacteria and lactobacilli. Bifidobacteria can be easily isolated and enumerated; culture-dependent and -independent counts were consistent. Selective media for fecal lactobacilli were unsuitable; plates, qPCR, FISH, and 16S HTS were gave inconsistent counts.